2016
DOI: 10.2527/jas.2016-0610
|View full text |Cite
|
Sign up to set email alerts
|

Predicting pork loin chop yield using carcass and loin characteristics

Abstract: The objective was to determine the predictive ability of carcass length for the number of equal-thickness chops obtained from a boneless pork loin. Longer pork carcasses are assumed to yield longer loins and, therefore, an increased number of chops. Loins were collected from pigs (1,238 total) raised under commercial conditions and marketed when the mean pig weight in a pen reached 138 kg. Pigs were slaughtered over 7 wk in a commercial facility. Carcass length was measured at 1 d postmortem on the left side o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
13
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 10 publications
6
13
1
Order By: Relevance
“…Results from Man-Whitney tests showed that alpha diversity at all stages were different ( P < 0.001) to each other. This was in accordance with similar studies in pigs and other organisms (Frese et al, 2015; Guevarra et al, 2019); Lu et al, 2018). The increase in alpha diversity with age was similar to what previously found by different authors (Chen et al, 2017; Kim et al, 2011; Looft and Allen, 2012; Thompson et al, 2008).…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…Results from Man-Whitney tests showed that alpha diversity at all stages were different ( P < 0.001) to each other. This was in accordance with similar studies in pigs and other organisms (Frese et al, 2015; Guevarra et al, 2019); Lu et al, 2018). The increase in alpha diversity with age was similar to what previously found by different authors (Chen et al, 2017; Kim et al, 2011; Looft and Allen, 2012; Thompson et al, 2008).…”
Section: Resultssupporting
confidence: 94%
“…No change in genomic heritability were observed at weaning. The decrease in heritability for FD was similar to what found by Lu et al (2018) for similar traits. He et al (2016) also reported the significant contribution of microbiome in porcine fatness.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations